Lattice parameter evolution during heating of Ti-45Al-7.5Nb-0.25/0.5C alloys under atmospheric and high pressures. (November 2018) - Li, Xi; Dippenaar, Rian; Shiro, Ayumi; Shobu, Takahisa; Higo, Yuji; Reid, Mark; Suzuki, Hiroshi; Akita, Koichi; Funakoshi, Ken-Ichi; Liss, Klaus-Dieter
Abstract: Lattice strain evolution during deformation processing of Ti-Al alloys at high temperature is important in terms of its microstructural evolution and microstructural stability. It is shown here that careful evaluation of lattice parameters is critical for the understanding of thermal expansion, crystallographic order, chemical composition and response to pressure, allowing to identify phase transitions and segregation, in addition to the measurement of the more conventional quantities phase composition and order parameter. The lattice parameters of Ti-45Al-7.5Nb-0.25/0.5C (at. %) alloys were calculated using both Rietveld and single peak fitting methods from data obtained by in-situ synchrotron diffraction experiments at high temperature under atmospheric and high pressure respectively. The lattice strain evolution as a function of temperature in a Ti-45Al-7.5Nb-0.25C (at. %) alloy under high pressure was compared with that of a Ti-45Al-7.5Nb-0.5C (at. %) alloy heated under atmospheric pressure. The contribution of each of the four lattice strain factors is semi-quantitatively assessed in the temperature range investigated. Highlights: Lattice strain of Ti-Al intermetallics at ambient pressure depends on thermal expansion, composition and order parameter. Pressure has a determining influence on lattice strain evolution and transformation temperatures. A new version of the sequence of phase changes occurring is proposed, based on experimental data at high pressure. The c/a ratios of both α2 - and γ-phases indicate the extent to which these phases are ordered.